Bioactivity of carotenoid produced by soft coral symbiotic microorganisms from Panjang and Karimunjawa Island, Central Java, Indonesia - Lia Kusmita; Handung Nuryadi; Prasetyo Abi Widyananto; SAKTI MUCHLISSIN; Agus Sabdono; Agus Trianto; Ocky Karna Radjasa (Society for Indonesian Biodiversity, 2021)
Abstract. Kusmita L, Nuryadi H, Widyananto PA, Muchlissin S, Sabdono A, Trianto A, Radjasa OK. 2021. Bioactivity of carotenoid produced by soft coral symbiotic microorganisms from Panjang and Karimunjawa Island, Central Java, Indonesia. Biodiversitas 22: 732-740. The diversity of soft corals is more varied in waters. One of the characteristics of soft corals is the production of secondary metabolites, i. i.e. carotenoids. Carotenoids are phytonutrients found in the cells of a wide variety of plants, algae, and bacteria as secondary metabolic compounds with antioxidant functions. Carotenoid biosynthesis is strongly influenced by the environment in which the producing organism grows. This study was aimed to uncover the antioxidant and anti-ultraviolet activities of carotenoids produced by soft coral symbiotic microorganisms in the waters surrounding the Panjang and Karimunjawa Islands in the North Java Sea, Indonesia. The parameters observed included water quality, antioxidant activity, and anti-ultraviolet activity. The results indicated that the water quality at Panjang Island did not meet quality standards (including salinity, visibility, dissolved oxygen, ammonia, and nitrate) while that at Karimunjawa did. The diversity of soft corals was more varied at Karimunjawa Island than at Panjang Island. In contrast to the bioactivity, the carotenoid extracts from the Panjang Island soft coral symbiotic microorganisms showed higher activity than those from Karimunjawa Island microorganisms. The highest antioxidant activity was found in the bacterial isolate 19.PP.Sc1.6 from Panjang Island and was identified based on the 16S rRNA gene as Virgibacillus salarius, with 99% similarity.